Socialist Television Drama, Newspaper Critics and the Battle of Ideas During the Crisis of Britain's Post-War Settlement. (11th March 2019) - Fielding, Steven
Abstract: Due to the difficult methodological issues it presents, political historians are wary of using television - the most important mass medium of the later twentieth century - as a means of exploring vernacular political thinking. Attempting to show how television audiences were encouraged to think politically, the article outlines a method generated through an engagement with the work of disciplines beyond history, to help political historians more systematically assess the medium's popular impact. The article takes as its case study Britain during the 1970s, one of the most ideologically contested periods in the country's history. It analyses how television critics employed by the Daily Mirror and Daily Express encouraged their millions of readers to respond to the dramas of socialist playwrights Jim Allen and Trevor Griffiths, thereby giving historians an insight into the shape of those conversations spawned by their work, such private dialogues being the place where the full political meaning of television was ultimately created.